Conductivity and dynamic mechanical studies of PVC/PEMA blend polymer electrolytes - Zakaria, N.A.; Yahya, S.Y.S.; Isa, M.I.N.; Mohamed, N.S.; Subban, R.H.Y. (2009)
The ionic conductivity and mechanical properties of poly (vinyl chloride) (PVC)/poly (ethyl methacrylate) (PEMA) polymer blends containing LiN(CF3S03h as doping salt has been studied using electrical impedance spectroscopy (EIS) and Dynamic Modulus Analysis (DMA) as a function of polymer blend ratios and lithium salt concentration. The film with PVC/PEMA composition of 65 :35 obtained the highest conductivity with good transparency. DMA showed that both the storage modulus (E') and the glass transition temperature (Tg) of the PVC/PEMA is increased with PEMA concentration. In the case of PVC/PEMA-LiN(CF3S02)2 films, the conductivity was found to increase with concentration of salt added with a maximum in conductivity at 35 wt.% LiN(CF3S02h. The Tg values of the doped films was found to increase with concentration of salt such that the film with the highest conductivity value has the highest Tg.